2023
DOI: 10.15379/ijmst.v10i4.1856
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Gate of the Melaka Sultanate

Fauzan Mustaffa,
Ziad Baydoun,
Mohamad Izani Zainal Abidin
et al.

Abstract: Based on the historical Malay, China and Arab textual account, there was a primary gate that marked the entrance to the royal compound of Melaka Sultanate before 1511. The primary gate was arguably among the most iconic construct and strategic to the Sultanate city, at security, socio-cultural, symbolic and aesthetic levels. However, no critical study has been conducted in tracing the form, position, and its relation to the municipality of the Sultanate Melaka City. This study employs narrative analysis framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…ii) The "Explanation" phase, which adopts an objectivist stance to comprehend historical texts. This phase delves into 'external criticism,' considering the authors' perspectives and employing rhetorical analysis to uncover the underlying motivations and interests that shape their pursuit of knowledge [14]. iii) The "Exploration" phase, which endeavors to establish connections based on the overarching narrative and its correlation with the analysis conducted through the visual anthropological framework.…”
Section: Narrative Analysis Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…ii) The "Explanation" phase, which adopts an objectivist stance to comprehend historical texts. This phase delves into 'external criticism,' considering the authors' perspectives and employing rhetorical analysis to uncover the underlying motivations and interests that shape their pursuit of knowledge [14]. iii) The "Exploration" phase, which endeavors to establish connections based on the overarching narrative and its correlation with the analysis conducted through the visual anthropological framework.…”
Section: Narrative Analysis Frameworkmentioning
confidence: 99%
“…This approach aimed to identify any remnants of Melaka Sultanate structures, essentially using them as markers. Over the course of the research, the study identified a sequence and alignment of significant locations, such as the primary street passing through Bendahara village, the Sultanate bridge, and the Sultanate gate, based on historical texts [13] & [14]. In the second phase of the study, the focus shifted to creating an inventory with critical annotations.…”
Section: Table 1 a Simplified Framework Of Visual Anthropological Ana...mentioning
confidence: 99%